Limited protective properties of thymol and thyme oil on differentiated PC12 cells with downregulated Mgst1 - Sobczak, Monika; Kalemba, Danuta; Ferenc, Bozena; Zylinska, Ludmila (Journal of Applied Biomedicine, 2014)
In this study we analyzed molecular mechanisms of antioxidative protection of thymol and thyme oil using differentiated PC12 cells, a widely accepted neuronal model. Thymol due to multiple functions is commonly used for clinical applications. However, its action on nervous tissue remains poorly understood. We evaluated the effect of 24 h incubation of the cells with thymol (100 and 400 μM) and equivalent content of thyme oil. Microsomal glutathione transferase 1 (Mgst1) is an important player in anti-oxidative protection because of its transferase and peroxidase activities. Since its expression decreases during aging, we also used stable transfected cells with downregulated Mgst1 (PC12_M). We analyzed cell viability, lipid peroxidation level, glutathione content and expression of key enzymes responsible for cellular reduced glutathione – catalytic subunit of γ-glutamylcysteine ligase and glutathione reductase. Whereas thymol and thyme oil improved antioxidant capacity of control cells, diminished protection was observed in PC12_M line. Increasing interest in natural dietary components has focused attention on plants used as a rich source of bioactive phytochemicals. However, currently available information on the safe amount for thyme oil using appears to be insufficient. Our results indicate that the thyme oil should be used with caution, especially by elderly people.
Keywords: thymol; Glutathione; techniky in vitro; antioxidancia; Glutathione Transferase; PC12 Cells; Thymus Plant; Antioxidants; Plant Oils; Lipid Peroxidation; Aging; Neurons; Thymus (rostlina); Cell Survival; Thymol; viabilita buněk; Statistics as Topic; oleje rostlin; buňky PC12; peroxidace lipidů; statistika jako téma; glutathion; neurony; In Vitro Techniques; stárnutí; glutathiontransferasa